2010
DOI: 10.1111/j.1095-8649.2010.02677.x
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of the round stingray Urobatis halleri (Elasmobranchii: Rajiformes) in southern California and the Gulf of California

Abstract: The round stingray, Urobatis halleri, is a viviparous elasmobranch that inhabits inshore, benthic habitats ranging from the western U.S.A. to Panama. The population genetic structure of this species was inferred with seven polymorphic microsatellite loci in samples collected at three sites in coastal southern California, one near Santa Catalina Island, California and one in the eastern Gulf of California. Urobatis halleri is relatively common, but little is known of its movement patterns or population structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…It is arguable that in highly mobile elasmobranch species such as pelagic sharks and mobulid rays, conservation efforts have to be conducted at the regional scale (e.g., Ovenden et al, 2009). Because of sharp geographic composition synonymous to limited genetic exchange between local populations, N. kuhlii and other (Chevolot et al, 2006;Dudgeon et al, 2009;Plank et al, 2010;Ovenden et al, 2011;present study) and 27 coastal teleost fish species (black diamonds) (Blanquer et al, 1992;Borsa, 2003;Borsa et al, 1997a;Fauvelot and Borsa, 2011;Francisco et al, 2011;Gaither et al, 2011;González-Wangüemert et al, 2010;Hemmer-Hansen et al, 2007;Hoarau et al, 2002;Horne et al, 2011;Jones et al, 2010;Kotoulas et al, 1995;Magsino and Juinio-Meñez, 2008;Matschiner et al, 2009;McCusker and Bentzen, 2010;Mobley et al, 2010;Muths et al, 2011;Planes and Fauvelot, 2002;Puebla et al, 2009;Purcell et al, 2009;Rohfritsch and Borsa, 2005;Roldán et al, 1998;Rolland et al, 2007;Timm et al, 2012). Other details in Supplementary material, Table S7.…”
Section: Implications For Managementmentioning
confidence: 99%
“…It is arguable that in highly mobile elasmobranch species such as pelagic sharks and mobulid rays, conservation efforts have to be conducted at the regional scale (e.g., Ovenden et al, 2009). Because of sharp geographic composition synonymous to limited genetic exchange between local populations, N. kuhlii and other (Chevolot et al, 2006;Dudgeon et al, 2009;Plank et al, 2010;Ovenden et al, 2011;present study) and 27 coastal teleost fish species (black diamonds) (Blanquer et al, 1992;Borsa, 2003;Borsa et al, 1997a;Fauvelot and Borsa, 2011;Francisco et al, 2011;Gaither et al, 2011;González-Wangüemert et al, 2010;Hemmer-Hansen et al, 2007;Hoarau et al, 2002;Horne et al, 2011;Jones et al, 2010;Kotoulas et al, 1995;Magsino and Juinio-Meñez, 2008;Matschiner et al, 2009;McCusker and Bentzen, 2010;Mobley et al, 2010;Muths et al, 2011;Planes and Fauvelot, 2002;Puebla et al, 2009;Purcell et al, 2009;Rohfritsch and Borsa, 2005;Roldán et al, 1998;Rolland et al, 2007;Timm et al, 2012). Other details in Supplementary material, Table S7.…”
Section: Implications For Managementmentioning
confidence: 99%
“…The explanation for heterogeneity among islands, some of which were <100 km apart, was that the channels >500 m deep between the islands prevented gene flow. Studies of the round stingray Urolophus halleri (Cooper 1863) in the same region found much greater heterogeneity between the California mainland and offshore islands than was seen over comparable distances along the mainline coast (Plank et al , 2010). Phillips et al (2011) detected significant mtDNA heterogeneity in three species of sawfishes ( Pristis ) between the Gulf of Carpentaria and the west coast of Australia and concluded that dispersal in sawfishes was limited, at least for females.…”
Section: Population Structure and Sub‐structurementioning
confidence: 99%
“…2003; Plank et al. 2010). Similar to S. pulcher and U. halleri , M. henlei is commonly collected at depths between 60 m and 200 m throughout its distribution (Ebert 2003), a range of depths that may allow the species to swim beneath the warm surface waters of the Cape and to disperse around the Cape of the Baja California Peninsula resulting in the population connectivity observed in the present study between sample localities on both sides of the Peninsula (Table3 and Fig 3…”
Section: Discussionmentioning
confidence: 99%